Performance Test of Methylene Blue Degradation Using TiO₂–Graphene Oxide Composite Synthesised from Coconut Shells - Heltina, Desi; Fesya Putri, Andini; Fauziyah, Hidayatul; Peratenta Sembiring, Maria; Amri, Amun; Tao Jiang, Zhong (Rekayasa, 2025)
Industry produces textile liquid waste which contains dangerous compounds such as methylene blue which can damage the environment. One effective method to overcome this problem is to use a TiO2 nanocomposite-based photocatalyst modified with Graphene Oxide (GO). GO is obtained from the synthesis of coconut shells, which is a biomass waste. This research aims to synthesize and display the performance of a TiO2/Graphene Oxide composite photocatalyst from coconut shells in degrading methylene blue. The TiO2/Graphene oxide nanocomposite synthesis method begins by carbonizing coconut shells to form graphite. Carbonization removes volatile compounds and produces a rich carbon structure, which is the initial requirement for the formation of GO. Synthesis of GO from graphite using the Hummer method. Synthesis of TiO2/Graphene oxide composite using a solvothermal process with various GO mass ratios. The performance of the photocatalyst was tested for degradation using methylene blue. Analysis of the TiO2/Graphene Oxide Composite using XRD, FTIR, SEM, BET characterisation and UV-Vis Spectrophotometer. The results show that at GO of 15%, the composite showed the highest surface area and optimal anatase crystallinity, resulting in the best degradation efficiency (70%). Graphene Oxide is synthesized from coconut shell biomass waste. This research shows that the TiO₂–Graphene Oxide composite has high efficiency in degrading dangerous synthetic dyes from textile industry wastewater through an efficient photocatalytic mechanism. This composite application is an application of technology that contributes directly to achieving the Sustainable Development Goals (SDGs), especially SDG 6 (Clean Water and Adequate Sanitation), through the development of sustainable, efficient and environmentally friendly waste processing technology.